Hubungan Antara Pendidikan Karakter Dengan Perilaku Pergaulan Bebas di SMK Negeri 1 Bokan Kepulauan Kabupaten Banggai Laut - Abd. Muin Kenta; Rosmina Rosmina; Moh. Fahri Haruna; Sucy Pratiwi Maliki (Jurnal Biologi Babasal, 2022)
Abstract : Considering that character education is important to give to students, but the lack of knowledge and application of character education is very worrying because of the many acts of free association that occur among students as the next millennial generation. The purpose of this study was to determine the relationship between character education and the free association behavior of students at SMK Negeri 1 Bokan Kepulauan, Banggai Laut Regency. This research was quantitative descriptive research which looks at the correlation or relationship between variables. The researcher conducted this research at SMK Negeri 1 Bokan Kepulauan, Banggai Laut Regency in July - August 2022. The population and sample were students of class X and XI, and the researcher took all the population to be used as research samples because of the population only consisted of 24 students. Data collection techniques used in this research was questionnaire. Data analysis used descriptive analysis and inferential statistics, namely simple regression analysis, product moment correlation analysis, and also ANOVA analysis. Based on the results of data analysis, it was concluded that there was a very low relationship (0.171, category 0.00–0.199) between the students’ character education and their free association behavior at SMK Negeri I Bokan Kepulauan Banggai Laut Regency. Keywords: Character Education, Free Association, Promiscuous sex